Territorial Governance Local Development, Rural Areas and Agrofood Systems - Torre, André; Traversac, Jean-Baptiste (Physica-Verlag HD, 2011)
This work aims to present the most recent developments regarding territorial governance, placing particular emphasis on rural and periurban areas. The reader will find information on the processes of development of European regions, as well as on the behaviours and strategies adopted by the different actors who live in these territories and contribute to the latter's livelihood. The first part of the book analyses the structural changes in the modes of production that have affected these territories. The second part addresses the questions of methodology and of the structures of governance of local development in rural areas. The last section makes an assessment of the geographical indications as tools of governance of local agrifood chains. The book was written by economists, geographers, land use planners and specialists of the questions of governance and management of rural and periurban areas.